O ścisłych związkach pedagogiki z etyką - Leś, Tomasz (Hybris, 2017)
The purpose of this paper is to provide grounds for the thesis on close relations between pedagogy and ethics. These relations can be both accidental and necessary in their form, however, the latter are definitely more significant in terms of implications for the pedagogy as a discipline. This is because pedagogy can be considered as (practical) ethics. The thesis will be supported by reference to both practical and strictly philosophical arguments. The final part of the paper will show the consequences of this specific identification of the aforementioned relations for pedagogy as a discipline.